PENGUATAN CIVIC LITERACY MAHASISWA MELALUI LITERASI DIGITAL DENGAN PENDEKATAN DESIGN-BASED RESEARCH - Kristiawan, Indria; Umamy, Etty; Hariati, Tunik (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study aims to analyze the strengthening of students’ civic literacy through the integration of digital literacy in learning using a Design-Based Research approach. Strengthening civic competence has become increasingly important in the digital era as students are exposed to a vast flow of information that requires critical, analytical, and responsible thinking in understanding public issues. This research employed a qualitative approach with a Design-Based Research design implemented through several stages, including needs analysis, development of a digital literacy-based learning design, implementation of the learning process, and reflection on the learning outcomes. The research subjects were students of Universitas Wisnuwardhana selected purposively based on their participation in learning activities integrating digital literacy. Data were collected through observation, interviews, and documentation, and analyzed using qualitative data analysis techniques consisting of data reduction, data display, and conclusion drawing. The findings indicate that the integration of digital literacy in learning encourages students’ active engagement in analyzing public information, developing critical thinking skills, and constructing rational arguments in civic discussions. The Design-Based Research approach enables the development of adaptive and contextual learning designs that support the strengthening of students’ civic literacy in higher education settings. The results of this study provide practical implications for the development of innovative civic education learning that is relevant to the digital era and contributes to improving the quality of higher education oriented toward twenty-first century competencies.